Biology of Cicadulina species (Homoptera: Cicadellidae) and transmission of maize streak virus - Asanzi, M.C.; Bosque Pérez, N.A.; Nault, L.R.; Gordon, D.T.; Thottappilly, G. (1995)
The survivorship, fecundity and development time (egg to adult) of Cicadulina storeyi China, C. arachidis China and C. ghaurii Dabrowski were studied at three constant temperatures (20, 25 and 30 .C). Additional tests were conducted to descriptionbe maize streak virus (MSV) transmission by C. arachidis and C. ghaurii and to compare virus transmission efficiency of these two species with that of C. storeyi and C. mbila (Naude).